2012
DOI: 10.1111/j.1600-0897.2012.01156.x
|View full text |Cite
|
Sign up to set email alerts
|

Inherited Thrombophilia and IVF Failure: The Impact of Coagulation Disorders On Implantation Process

Abstract: In connection with the embryo acceptance process after IVF procedure, endometrial cells surface receptors, extracellular matrix (ECM) molecules, endothelium and blood circulation factors were involved in remodelling of endometrium. Plasminogen activator inhibitor type 1 plays a significant role during the early phases of placental vascular remodelling and regulates the trophoblast invasion through controlling plasmin activity. Endometrial cell surface protein integrin alphaV/beta3, responsible for the adhesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 86 publications
2
36
0
Order By: Relevance
“…Other changes within the clotting process around the time of embryo implantation are an increase in tissue factor, an activation of the extrinsic coagulation cascade, and an increase in requirement for methylation from folic acid. Hence, inherited abnormalities of the clotting system such as the prothrombin gene mutation, factor V Leiden, methyltetrahydrofolate reductase (MTHFR), and protein S and C and anti-thrombin III would be expected to have a significant influence on implantation and the early pregnancy (164). Although the appropriate treatment is not clear, except for women with the anti-cardiolipin syndrome, where appropriate treatment must commence at conception is widely accepted (274).…”
Section: Thrombophiliamentioning
confidence: 99%
See 1 more Smart Citation
“…Other changes within the clotting process around the time of embryo implantation are an increase in tissue factor, an activation of the extrinsic coagulation cascade, and an increase in requirement for methylation from folic acid. Hence, inherited abnormalities of the clotting system such as the prothrombin gene mutation, factor V Leiden, methyltetrahydrofolate reductase (MTHFR), and protein S and C and anti-thrombin III would be expected to have a significant influence on implantation and the early pregnancy (164). Although the appropriate treatment is not clear, except for women with the anti-cardiolipin syndrome, where appropriate treatment must commence at conception is widely accepted (274).…”
Section: Thrombophiliamentioning
confidence: 99%
“…It has been unclear whether an inherited thrombophilia leading to microthrombi within the decidua are associated with implantation failure of the embryo as the intervillous spaces are not developed until 10 wk of gestation (164). Although it is tempting to speculate that perturbations in the clotting system may influence implantation and early embryonic development, for example, factor XII gene expression is increased in endometrial stromal cells during in vitro decidualization, this is believed to lead to an activation of the kallikrein-kininogen-kinin system during the implantation of human embryos (175).…”
Section: Thrombophiliamentioning
confidence: 99%
“…Moreover, the prevalence of homozygous PAI-1 4G/4G polymorphism was demonstrated to be higher in patients with RIF and RPL [19]. It was also reported that low molecular weight heparin and metformin have been demonstrated to improve implantation process and ameliorate pregnancy complications in patients with 4G/4G genotype because of the hypofibrinolytic impact of overexpressed PAI-1 on implantation [20].…”
Section: Discussionmentioning
confidence: 94%
“…In a recent pilot study of 60 strictly selected women with unexplained recurrent IVF-ET failures excluding all cases with other known risk factors, we reported an increased occurrence of carriers of the Gpllla-PIA2 allele, in comparison with a control group of 60 fertile women with no history of pregnancy or vascular complications, resulting in an odd ratio of 2.9 and a stronger association for the younger participants [10]. Furthermore, in a previous study in Bulgaria, Ivanov et al [8] also found a 2.6-fold increased risk during the comparison of 67 women with IVF-ET failures with 96 fertile controls [11]. The only study so far that has not concluded in a positive finding regarding the role of Gpllla-PIA2 allele in pathogenicity of IVF-ET failure was a small underpowered study of 42 women with recurrent IVF-ET failure and 20 fertile controls in which no analytical statistical analysis was cited [12].…”
mentioning
confidence: 78%
“…However, glycoprotein llla (integrin beta3) participates in the process of the implantation not only involved in platelet aggregation but also as a subunit of integrin alphaVbeta3 which is present in the interactions of endometrial and embryonic cells [11].…”
mentioning
confidence: 99%